Effect of strain rate sensitivity in visco-plastic modeling. (November 2018) - Chapuis, Adrien; Liu, Qing
Abstract: Many crystal plasticity models use a rate sensitive law for its convenience. The rate sensitivity can be determined experimentally and input in the models. From a numerical point of view, high values of the strain rate sensitivity parameter m favor easy convergence of these models, but when m is fixed arbitrarily, which is in practice done for slightly rate sensitive materials, the physical meaning of m is lost. The present study shows that the flow stress σ, slip systems activity γ s, strain anisotropy and simulated texture are strongly dependent on m . Precautions should be taken when predicting the mechanical behavior of polycrystals. To simulate nearly rate insensitive materials with models using a rate sensitive law, the use of the reference shear strain γ ˙ 0 equal to the imposed strain rate is necessary but not sufficient. It is also necessary to use a high strain rate sensitivity parameter ( m  = 0.05) to correctly evaluate the material parameters, i.e., the critical resolved shear stresses (CRSS). This study also provides a relationship between the CRSS determined for different values of strain rate ɛ ˙, m and γ ˙ 0, so that CRSS determined in different studies can be compared.